Antibiotic overuse in pediatric dental pain management in Saudi Arabia: A cross-sectional survey of prescriber KAP, digital solutions, and financial influences - Qamar, Zeeshan; Alajmi, Hanoof Khaled Saad; AlKandari, Dalal Waleed Hassan; Aman, Fatma Emad Sultan (Edelweiss Applied Science and Technology, 2026)
This cross-sectional survey investigated the knowledge, attitudes, and practices (KAP) of dental practitioners in Saudi Arabia regarding antibiotic prescribing for pediatric dental pain, while also exploring digital readiness and financial influences. A nationally representative sample of 676 dentists completed a validated questionnaire. Results revealed a significant gap between knowledge and practice. While awareness of antimicrobial resistance was high (93.7%), adherence to specific guidelines was poor; for instance, only 27.1% correctly rejected antibiotics for uncomplicated pulpitis. Practice setting was a key influencer, with private practitioners reporting significantly higher parental pressure and being more likely to inappropriately prescribe antibiotics. Attitudinal barriers included fears of complications and medico-legal issues. Although digital support tools were viewed favorably (87.5%), major implementation barriers were time constraints (84.7%) and financial costs (67.9%). The study concludes that inappropriate antibiotic prescribing in Saudi pediatric dentistry is driven by a complex interplay of knowledge deficits, external pressures, and systemic barriers. Targeted interventions are urgently needed, including continuous education, antimicrobial stewardship programs, and the integration of user-friendly digital decision-support systems to bridge the knowledge-practice gap and combat antimicrobial resistance.